Progressive Wavelet Coding of Images - Malvar, Henrique S. (1999)
Fast and efficient image compression can be achieved with the progressive wavelet coder (PWC) introduced in this paper. Unlike many previous wavelet coders, PWC does not rely on zerotrees or other ordering schemes based on parent-child wavelet relationships. PWC has a very simple structure, based on two key concepts: (1) data-independent reordering and blocking, and (2) low-complexity independent encoding of each block via adaptive Rice coding of bit planes. In that way, PWC allows for progressive image encoding that is scalable both in resolution and bit rate, with a fully embedded bitstream. PWC achieves a rate vs. distortion performance that is comparable to that of the state-of-the-art SPIHT (set partitioning in hierarchical trees) coder, but with a better performance/complexity ratio.